Ligand modulates the conversion of DNA-bound vitamin D3 receptor (VDR) homodimers into VDR-retinoid X receptor heterodimers. - Cheskis, B (1994)
Protein dimerization facilitates cooperative, high-affinity interactions with DNA. Nuclear hormone receptors, for example, bind either as homodimers or as heterodimers with retinoid X receptors (RXR) to half-site repeats that are stabilized by protein-protein interactions mediated by residues within both the DNA- and ligand-binding domains. In vivo, ligand binding among the subfamily of steroid receptors unmasks the nuclear localization and DNA-binding domains from a complex with auxiliary factors such as the heat shock proteins. However, the role of ligand is less clear among nuclear receptors, since they are constitutively localized to the nucleus and are presumably associated with DNA in the absence of ligand. In this study, we have begun to explore the role of the ligand in vitamin D3 receptor (VDR) function by examining its effect on receptor homodimer and heterodimer formation. Our results demonstrate that VDR is a monomer in solution; VDR binding to a specific DNA element leads to the formation of a homodimeric complex through a monomeric intermediate. We find that 1,25-dihydroxyvitamin D3, the ligand for VDR, decreases the amount of the DNA-bound VDR homodimer complex. It does so by significantly decreasing the rate of conversion of DNA-bound monomer to homodimer and at the same time enhancing the dissociation of the dimeric complex. This effectively stabilizes the bound monomeric species, which in turn serves to favor the formation of a VDR-RXR heterodimer. The ligand for RXR, 9-cis retinoic acid, has the opposite effect of destabilizing the heterodimeric-DNA complex. These results may explain how a nuclear receptor can bind DNA constitutively but still act to regulate transcription in a fully hormone-dependent manner.